Thorny Roads of Scholarly Communication: An Evaluation on the Publication Process of Articles - Umut Al; İpek Şencan (Türk Kütüphaneciliği)
Publication process of an article can be as tiresome and as long as its preparation process. Publication process of articles can vary not only among the disciplines but also according to the journals within the same discipline. Some researchers send their articles to journals without having knowledge about the publication process and face with problems due to the length of the process. It is advantageous for every researcher in every field to have knowledge about the attitude of the journals in their field during the scholarly communication process. In this study, article publication processes of information science journals have been examined. In this context, we tried to answer questions such as; what is the duration between the time that the articles are received and published in information science journals? Can the publication duration of articles differentiate between the information science journals? Which journals publish the fastest the articles in the field of information science and which journals have the longest publication process? Within the scope of our study, 1939 articles within 30 information science journals, which are parts of the Journal Citation Reports (JCR) and have the capacity to answer our research questions, have been examined. In the direction of the study’s purpose, elapsed time between the reception and revision, reception and acceptance, reception and publication, revision and acceptance, revision and publication, acceptance and publication of the articles have been calculated day-denominated. After the assessment of information science articles, it is found out that the longest time is between the reception-revision, compared to revision-acceptance and acceptance-publication. Publication process of the articles that are sent to information science journals last about nine months and this duration differentiate significantly according to journals. While the journals such as Information Systems Research, Information Society, Information and Organization, and Information and Management are among the ones that has the longest article publication process, Journal of Academic Librarianship, Scientometrics, Telematics and Informatics, and Journal of Informetrics are among the journals that have the fastest article publication process. Extension of the publication process of the articles brings several problems with itself. This problem should be taken into consideration carefully by the relevant people and possible solutions should be searched and discussed.